Equation of state studies of warm dense matter samples heated by laser produced proton beams - Hoarty, D; Guymer, T; James, S; Gumbrell, E; Brown, C; Hill, M; Morton, J; Doyle, H (2012)
Heating of matter by proton beams produced by short pulse, laser-solid target interaction has been demonstrated over the last ten years by a number of workers. In the work described in this paper heating by a pulse of laser produced protons has been combined with high-resolution soft x-ray radiography to record the expansion of thin wire targets. Analysis of the radiographs yields material properties in the warm dense matter regime. These measurements imply initial temperatures in the experimental samples over a range from 14 eV up to 40 eV; the sample densities varied from solid to a tenth solid density. Assuming an adiabatic expansion after the initial proton heating phase isentropes of the aluminium sample material were inferred and compared to tabulated data from the SESAME equation of state library. The proton spectrum was also measured using calibrated magnetic spectrometers and radiochromic film. The accuracy of the technique used to infer material data is discussed along with possible future development. © 2011.